Novel light and tough ZrB2-based functionally graded ceramics. (15th August 2016) - Silvestroni, Laura; Capiani, Claudio; Dalle Fabbriche, Daniele; Melandri, Cesare
Abstract: Functionally graded materials (FGM) based on ZrB2 and containing SiC chopped fibers from 5 to 50 vol% are produced by powder metallurgy and hot pressing. An additional MoSi2 -ZrB2 outermost layer is added to improve the oxidation resistance. Besides, to prevent SiC fibers from detrimental reactions with MoSi2 during sintering, a ZrB2 -based buffer layer is sandwiched between the fiber-rich bulk and the outer MoSi2 -containing scale. The fibers in the optimized architecture are efficaciously protected during the sintering stage and effectively toughen the matrix. The FG composite has a density as low as 3.65 g/cm 3, nearly halved compared to pure ZrB2, and fracture toughness around 5–6 MPa·√m, doubled as compared to monolithic ZrB2 . In addition, preliminary oxidation tests at 1650 °C reveal that the outermost ZrB2 scale effectively protects the fiber from oxidation, thanks to the tailored doping with MoSi2 and Si3 N4 . Graphical abstract: Highlights: Production of ZrB2 -based FGM by powder metallurgy and one step hot pressing. Bulk with increasing volumetric fraction of discontinuous SiC fibers to increase the toughness of ZrB2 . An oxidation resistance outermost scale containing MoSi2 efficiently protected the fibers during oxidation at 1650 °C. A buffer layer in-between prevented detrimental reactions between Mo-compounds and the fibers during sintering. The best FGM had density of 3.65 g/cm 3 and toughness approaching 6 MPa·√m with improved failure tolerance behavior.